2022
DOI: 10.1155/2022/1027895
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of DNAJC12 Inhibited Tumorigenesis of Rectal Cancer via Downregulating HSPA4 Expression

Abstract: Background. Dysregulation of DnaJ heat shock protein family (HSP40) member C12 (DNAJC12) is implicated in the malignancy progression of multiple cancers. The current study aimed to determine the biology function and mechanism of DNAJC12 in rectal cancer (RC). Methods. RC tissues, adjacent tissues, RC cell lines, and normal colorectal epithelial cell lines were collected to analyze DNAJC12 expression. The abilities of DNAJC12 on proliferation, migration, and apoptosis of RC cells were detected by CCK-8, wound h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%